Pembelajaran SKI di MIS Nurul Fadhillah - Nasution, Abdul Gani Jamora; Siregar, Amelia Rika Fadillah; Putriana, Alda; Rahman, Aulia; Siregar, Rahma Fadillah; Daulay, Siti Amalia (TSAQOFAH, 2023)
This article describes the teacher's strategy in choosing variations of methods on SKI learning as well as describing the responses of students on the methods used on SKI learning. Education is a conscious and planned effort to realize the learning atmosphere and learning process so that didiksecara participants are active in developing their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed by themselves, society, nation and state (Indonesian Law No. 20 of 2003 Article 1 National Education System, 2016). The purpose of the researcher so that mengetahaui can get the concept and method used by MI teachers when teaching SKI. Modern learning conception demands creative, responsive and active students in seeking, choosing and finding, analyzing, concluding, and reporting learning outcomes. Learning models like this can only be done well if the teacher is able to develop an effective learning strategy. For this reason, creativity of the teacher is needed in choosing effective learning methods. Therefore, it is necessary to study the importance of using methods in learning, because the method is very helpful in achieving learning goals. Based on the goals and background above, the method used in this study is a qualitative research method which has data collection technique using interview techniques, observations, and documentation.